DYNAMIC ANALYSIS OF A BALL-WEDGE DRIVE IN THE ZONE OF SMALL DISPLACEMENTS - ZAIKA, SERHII; SHCHERBINA, KYRYL; MAZHARA, VITALII; TORCHILOV, DANYLO; MASLIANIKOV, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Improvement of the functional indicators of machines, mechanisms and equipment, which has become widespread in modern mechanical engineering, is possible due to the improvement of finishing operations. One of the main indicators that will ensure the improvement of the functioning of hydraulic machines and the fuel system of internal combustion engines is the quality of manufacturing parts of their control equipment. Quality indicators in this case are surface roughness and the presence of macro irregularities. Ensuring the stipulated quality indicators in the process of hole processing at the finishing stages depends on hole honing. It is possible to influence the obtaining of stipulated quality indicators due to the flexibility of the hole honing process.The flexibility of the hole honing process lies in the possibility of varying the processing parameters depending on the existing geometric deviations. One of the main disadvantages of the existing hole honing process is the design of traditional honing heads, which are based on a press wedge, due to which the radial size is adjusted and the specific pressure is created on the surface being processed. It is also necessary to take into account the fact that the process of adjusting the radial size takes place in the zone of small movements, which involves the operation of the conditioned wedge of the traditional honing head within the transition from static to kinetic friction. The article proposes the design of the honing head, which provides for the transition from sliding friction to rolling friction with the provision of conditions for self-braking of the pressing wedge for the formation of specific pressure on the surface being processed.As a result of the conducted research, a comparison of the functioning of the traditional honing head and ball-wedge honing in dynamic conditions is given. The resulting transient and logarithmic-frequency characteristics indicate a reduction in the effect of friction forces on the process of adjusting the radial size during processing. Conditioned changes became possible due to the transition from sliding friction to rolling friction
Keywords: honing head; wedge kinematic pair; radial size control system; ball-wedge honing; transition characteristic; zone of small movements